2020
DOI: 10.1017/wet.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Critical timing of Palmer amaranth (Amaranthus palmeri) removal in sweetpotato

Abstract: Palmer amaranth is the most common and troublesome weed in North Carolina sweetpotato. Field studies were conducted in Clinton, NC, in 2016 and 2017 to determine the critical timing of Palmer amaranth removal in ‘Covington’ sweetpotato. Palmer amaranth was grown with sweetpotato from transplanting to 2, 3, 4, 5, 6, 7, 8, and 9 wk after transplanting (WAP) and maintained weed-free for the remainder of the season. Palmer amaranth height and shoot dry biomass increased as Palmer amaranth removal was delayed. Seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
(43 reference statements)
2
18
0
Order By: Relevance
“…emerged between the 13 and 27 DAP ratings, with greater abundance in diquat-only plots. Palmer amaranth has been reported to greatly reduce sweetpotato yield (Basinger et al 2019;Meyers et al 2010;Smith et al 2020), and its timing of emergence in this study occurred during the critical period for weed control of 2 to 6 WAP (Seem et al 2003;Smith et al in press).…”
Section: Treatment Bmentioning
confidence: 63%
“…emerged between the 13 and 27 DAP ratings, with greater abundance in diquat-only plots. Palmer amaranth has been reported to greatly reduce sweetpotato yield (Basinger et al 2019;Meyers et al 2010;Smith et al 2020), and its timing of emergence in this study occurred during the critical period for weed control of 2 to 6 WAP (Seem et al 2003;Smith et al in press).…”
Section: Treatment Bmentioning
confidence: 63%
“…Palmer amaranth is the most problematic weed in sweetpotato (Smith and Moore unpublished data;Webster 2010). Palmer amaranth can reduce marketable sweetpotato yield 80% to 95% if left uncontrolled (Barkley et al 2016;Basinger et al 2019;Meyers et al 2010a;Smith et al 2020). These yield reductions are factors of vigorous growth of Palmer amaranth (Horak and Loughin 2000;Meyers et al 2010a;Sellers et al 2003), high fecundity (Keeley et al 1987;Sellers et al 2003;Sosnoskie et al 2014), and resistance to many previously efficacious herbicidal modes of action (Heap 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meyers and Shankle (2015) reported that yellow nutsedge densities of 5 to 90 shoots m −2 in planted sweetpotato resulted in yield losses of 18-96%. Smith et al (2020) reported that Palmer amaranth, when not controlled, reduced 'Covington' marketable sweetpotato yield by 95% after season-long interference.…”
Section: Introductionmentioning
confidence: 99%
“…sweetpotato resulted in yield losses of 18-96%. Smith et al (2020) reported that Palmer amaranth, when not controlled, reduced 'Covington' marketable sweetpotato yield by 95% after season-long interference.…”
mentioning
confidence: 99%